Севастопольские рассказы - Толстой Лев Николаевич (Вагриус, 2004)
Экземпляры: Селтинская районная библиотека (аб) (20220929) / Инвентарный номер: 188546 / Цена: / Авт.знак: Т 53 / ГРНТИ: 17.82.32 / ББК: 84(2=411.2)